Asian Elephants: 15 years of research and conservation. (February 2020) - Hankinson, Emma; Nijman, Vincent; Abdullah,
Abstract: This document provides an overview of the research and conservation work that has been undertaken to date by our team at Oxford Brookes University in regard to Asian elephants. Research began in 2006, in collaboration with various NGO's from a range of countries (Indonesia, Malaysia, Myanmar), government agencies (Indonesia, Myanmar, Thailand, Sri Lanka) and local and international universities. Four major themes are recognised throughout our research; (1) the trade in live elephants, (2) the trade in elephant ivory and other body parts, (3) elephant distribution and abundance in Northern Sumatra, and (4) the wider conservation agenda of elephant conservation in Asia. The live trade in elephants concerns both the domestic trade (Indonesia, Thailand, Sri Lanka) and the international trade (Laos, Myanmar), and has a strong welfare component that needs to be addressed. The trade in ivory is still prevalent in Myanmar, Laos and Thailand, all with strong links to China, whereas the trade in ivory in Indonesia is more localised. The distribution mapping of elephants has so far been undertaken in Aceh and North Sumatra, and we will continue within this area of research in collaboration with Universitas Syiah Kuala. With respect to the wider conservation agenda of elephant conservation in Asia, many regions and most countries face similar opportunities and challenges. Lessons learned in countries such as Myanmar, Sri Lanka and Thailand, all with substantial elephant populations, need to be employed in Indonesia to better the conservation status of elephants and improve the lives of people that live side by side with the Asian elephant.